O Private equity como fator determinante ao bom desempenho em rankings qualitativos e quantitativos - Marzola, Márcio José (2015)
This study seeks an in-depth analysis of Private Equity in Brazil, more specifically from the perspective of how the article: the "Biggest and Best" ranking, by Exame magazine, reflects the subject, as well as a parallel profitability with CDI and Ibovespa. The methodology is to develop comparisons to quantify the presence of private equity funds in the magazine's ranking and to compare the price variation of post IPO stocks with the CDI and Ibovespa rate, the comparison will be the date of its IPO in a period next 30 to 360 days. For the experiment, we collected the IPOs in the year 2011 Bovespa the year 2013, a total of 24 IPOs. From these analyzes it can be concluded that the presence of Private Equity funds showed that the contribution by the investment funds is material to its IPO and the good future organizational performance, and explain that the purchase of shares at the time of IPO compared to the CDI and the Bovespa showed up in most of the observations that have equal returns or more profitable than the CDI and Ibovespa this in a short term and in the long term.